Pengembangan Hidung Elektronik untuk Klasifikasi Mutu Minyak Goreng dengan Metode Principal Component Analysis - Soca Baskara; Danang Lelono; Triyogatama Wahyu Widodo (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2016)
The existence of cooking oil which is mixed with dangerous material is very difficult to be detected by human olfactory system yet can be detected by sophisticated equipment. However, the equipment is very expensive and require an expert to operate it.Static system of electronic nose based on unselected gas sensor array has been built for classifying pure cooking oil’s odour and mixed cooking oil’s odour. Sensor array consist of sensor MQ-9, TGS-2600, MQ-2, TGS-2620, and TGS-822 along with a heat exchanger system that can reduce the temperature of sample’s odour. The sample chamber and sensor chamber are made from stainless steel with cylinder shape. The system tested by boiling the sample consist of each pure cooking oil form both palm and coconut oil with its mixture such as used lubricant, candle, and diesel fuel up to 300 0C to realese its odour. After the odour has been detected by electronic nose the next step is to classifying the data with PCA method.The result show that the response of sensor’s output is stable and the output of score plot from each pure cooking oil’s data from both palm and coconut oil can be well-classified from the mixed cooking oil.